Challenges of the Research and the Practice of Embodied: A Point of View from the Feldenkrais® Method of Somatic Education - Rose Eisenberg Wieder; Yvan Joly (Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación, 2016)
Somatic education is a new disciplinary field that focuses on the living body; consciousness exercised by the biological body and in the movement of the embodiment within the internal and external space. The Feldenkrais method (FM) and all the approaches of somatic education, have their own qualitative research needs to be reformulated, to identify their theoretical and scientific base, to measure the effects of their practices and to understand and improve the processes of training of practitioners and teachers. We must demonstrate the same paradox of a verbal inquiry into the non-verbal body and, if one wishes to do qualitative research of quality, the investigator must submit himself to the experience of awareness of its corporeality, – some proposals in this article if the reader ventures to perform them - therefore the somatic education proposes a particular form of qualitative research. Most of the points of view presented here, arise from the experience of Yvan Joly practitioner, trainer and researcher in education somatic and especially, as professor of the Feldenkrais Method associated with the "awareness of the body by the movement”. The integration of the ideas were carried out by Rose Eisenberg Wieder, ex-alumnae of Yvan Joly, current teacher and researcher education in the fields of training values for health and environment and teacher of the Feldenkrais method.